Aspek Rancangan Generator Magnet Permanen Fluks Radial Kecepatan Rendah - Suhada, Meggi Octa; Yasri, Indra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Permanent Magnet Synchronous Generator (PMSG) is one of the main wind power generation components that can be developed. In this research will be examined aspect of PMSG design based on MagNet Infolytica Trial Edition software is performed. Aspects of design that will be made refer to the stages to be performed on software Magnete Infolytica. The design using a combination of 18 slots 16 pole draft is then modeled on the MagNet Infolytica Trial Edition software. This generator has expected capacity 400 watts of power and 450 rpm of speed. The following step is to simulate the model design referring to the specifications mentioned at the beginning. By completing all the steps it can be concluded that Design proses on SolidWorks software is targeted for 1 set of slot and pole, then the design model will be extended to become a whole complete design import into the MagNet Infolytica software can be rotated, this proses able to save a lot of time of design, Choosing the correct size of mesh will impact to accuracy of the output waveform, either voltage, current or torque, The initial model simulation results are required some improvements, because of time efficiency matters, and The winding configuration is unique for each of slot and pole combinations. Hopefully by complied to the above overall stages the good result able to achieved.Keywords : MagNet Infolytica, PMSG, Generator, 18S16P